The Complete Mitochondrial Genome of the Caecal Fluke of Poultry, Postharmostomum commutatum, as the First Representative from the Superfamily Brachylaimoidea - Fu, Yi-Tian; Jin, Yuan-Chun; Liu, Guo-Hua (Frontiers in Genetics, 2019)
Postharmostomum commutatum (Platyhelminthes: Brachylaimoidea), a parasite of the caeca of poultry, has been frequently reported from many countries and regions, including China. However, the molecular epidemiology, population genetics and phylogenetics of this parasite are poorly understood. In the present study, we determined and characterized the complete mitochondrial (mt) genome of P. commutatum, as the first representative from the superfamily Brachylaimoidea. The mt genome of P. commutatum is a circular DNA molecule of 13,799 bp in size and encodes the complete set of 36 genes (12 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes) as well as a typical control region. The mt genome of P. commutatum presents a clear bias in nucleotide composition with a negative AT-skew on average (- 0.306) and a positive GC-skew on average (0.466). Phylogenetic analyses showed that P. commutatum (superfamily Brachylaimoidea) and other ten members of the order Diplostomida were recovered as sister groups of the order Plagiorchiida, indicating that the order Diplostomida is paraphyletic. This is the first mt genome of any member of the superfamily Brachylaimoidea and should represent a rich source of genetic markers for molecular epidemiological, population genetic and phylogenetic studies of parasitic flukes of socio-economic importance in poultry.